Association between the dietary inflammatory index and depressive symptoms in adults with metabolic syndrome: a cross-sectional study from the NHANES database - You, Jinshun; Xia, Shujie (Frontiers in Nutrition, 2025)
ObjectiveThe comorbidity of metabolic syndrome (MS) and depressive symptoms has emerged as a growing public health concern, contributing to a substantial global economic burden. The pathogenesis of this comorbidity is thought to be closely linked to inflammation. However, research examining the impact of the Dietary Inflammatory Index (DII) on depressive symptoms in adults with MS remains limited. This study aims to investigate the association between the DII and depressive symptoms in adults with MS, utilizing data from the National Health and Nutrition Examination Survey (NHANES).MethodsThis cross-sectional study included 7,553 participants aged 20 and older MS from six cycles of the NHANES (2007–2018). Depressive symptoms were assessed using the Patient Health Questionnaire scores, and dietary information was gathered to calculate the Dietary Inflammatory Index (DII). The association between DII scores and depressive symptoms in individuals with MS was evaluated through multivariable logistic regression analysis, adjusting for relevant covariates. Subgroup analyses and restricted cubic splines (RCS) were performed to explore this relationship further.ResultsAmong the participants, 907 individuals (12.0%) were identified as having depressive symptoms. After adjusting for all covariates, a positive correlation was observed (OR = 1.09, 95% CI: 1.04–1.14). After adjusting for all covariates, a positive association was observed between DII scores and depressive symptoms (OR = 1.09, 95% CI: 1.04–1.14). Individuals in the highest tertile of DII scores had significantly higher odds of depressive symptoms compared to those in the lowest tertile (OR = 1.36, 95% CI: 1.13–1.65). Subgroup analyses revealed that men were more likely to experience depressive symptoms among adults with MS. The RCS model revealed a nonlinear positive association between DII scores and depressive symptoms in these participants.ConclusionOur study indicates that the DII is positively correlated with an increased likelihood of depressive symptoms among adults with MS in the United States. These findings align with existing research and necessitate further validation through prospective cohort studies.